Chronic Kidney Disease Among Workers Exposed To Perfluorooctanoic Acid (PFOA) - Muhammad Ilyas; Andreas Kresna (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Background: Perfluorooctanoic acid (PFOA), a class of perfluorocarbons, are synthetic environmental contaminants. Their long biological half-lives and their poor ability to metabolize likely add to any chronic health effects they may pose, such as chronic kidney disease (CKD). The causal relationship between PFOA and CKD is still unclear, so it is necessary to look for some evidence regarding this relationship. The search for evidence is also complemented by a seven-step occupational disease assessment to establish occupational diseases. Aim: This study aims to justify chronic kidney disease of workers exposed to perfluorooctanoic acid can be diagnosed as occupational diseases.Methods: Searching literature for the evidence-based has been conducted with a clinical question through “PICO” method. Then continued with literature searching using the electronic database “PubMed”, “JSTOR”, and “Scopus” search engine. The keyword is “PFOA” “perfluoroalkyl substances” “perfluorooctanoic acid” “chronic kidney” “chronic kidney disease” “CKD” and combined with MeSH terms and Boolean operation. The inclusion criteria are research on humans, English language, and the exclusion is retracted articles.Result: From the five literatures obtained, there are differences in results. A study of workers exposed to perfluorooctanoic acid in a DuPont chemical plant with chronic kidney disease was (Standardized Mortality Ratios (SMR) = 3.11, 95% CI: 1.66, 5.32). Study in China found that perfluorooctanoic acid is not associated with renal function and higher risk of CKD (OR = 0.73, 95% CI: 0.57, 0.95; p=0.019).Conclusion: There are insignificant associations between perfluorooctanoic acid and chronic kidney disease.